Evaluation of the Effectiveness of ACK Filtering and ACK Congestion Control in Mitigating the Effects of Bandwidth Asymmetry - Marhoon, Haydar Abdulameer (2012)
The user demand for high speed and ubiquitous connectivity has led to the development and deployment of many new technologies, such as DSL and satellite-based networks, for accessing the Internet network. The goal of these technologies is to mitigate the bottleneck. Other technologies, such as wireless and packet radio networks aimed at providing the user with unrestricted access to their mobile devices and the Internet. Given that these networks are increasingly being deployed as high-speed access networks, it is highly desirable to achieve good network performance over such networks. These technologies show different characteristics (asymmetry) in uplink and downlink directions. Network asymmetry (uneven bandwidth) can negatively affect the performance of feedback-based transport protocol such as Transmission Control Protocol (TCP). This is because that congestion in any direction can affect the flow of feedback in the other direction. ACK Filtering and ACK Congestion Control techniques are used to diminish the congestion on the upstream link. These techniques suffer from sender burstiness and a slowdown in congestion window growth problems. This project addresses the TCP performance problems caused by network asymmetry and discuss the reasons for the inapplicability between TCP and asymmetric networks. It studies the effectiveness of these techniques in mitigating the effects of bandwidth asymmetry in TCP/IP networks and provides suggestions to overcome the problems associated with these techniques. Based on the performance model presented in this project, achieving optimum TCP performance under different asymmetric conditions is described.